Geoprocessamento x modernização da agricultura:estudo de dois distritos no município de Palmeira das Missões(RS) - Roberto Barboza Castanho; Roberto Cassol; Mari Lourdes Bezzi (Sociedade & Natureza)
The process of agricultural modernization that in happened in Rio Grande do Sul, begun in the decades of 1960 and 1970, it generated considerable transformations so much in the system of agricultural production as in the space reorganization of the areas returned to the primary section. This way, this research chose as laboratory of studies, two districts: Santa Teresinha and São Bento. The methodology was based on the accomplishment of bibliographical rising regarding the fear proposed, as well as field work. In this sense, the modernization process, analized in this research whit the support of geoprocessing technique, in the sense of verifying the current uses and occupations of both districts, came as an important instrument, in which cannot him to identify, the different space cuttings tha wa verified in elapsing of this research.